INOVASI MEDIA PEMBELAJARAN KEARSIPAN ELECTRONIK ARSIP (E-ARSIP) BERBASIS MICROSOFT OFFICE ACCESS - Saeroji, Ahmad (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
Microsoft Office Access (Ms Access) is a database management system which is a Relational Database Management System. The database in Microsoft Access is a set of objects consisting of tables, queries, forms, reports. Archival system is basically to store useful various files for organizations with the specific rules so the files can be found quickly and easily. Therefore; Microsoft Office Access is an appropriate breakthrough to build archival application systems based on Microsoft Office Access. It is not only easy to be operated but also available a package of Microsoft Office program. One of the most important benefits of the database is to facilitate the access to the data. The ease of accessing the data is the implication of the order data since it is the prerequisite of a good database. The database of archiving system is an application or system design which allows the archives storage digitally. The objective of the e-archives application program using Microsoft Access is to facilitate the delivery of material practices of electronic filing (e-archives). The purposes of the scientific study are: (1) to determine the basic concept and scope of Electronic archives (e-archives), (2) To know how to use the media of electronic archives (E-archives) aided Microsoft Office Access in the learning activities for Vocational students of Office Administration program.